Towards the 2024 Indonesian Elections: The Use of the Indonesian General Election Commission`s Twitter Account - Prabawa, Windhi Gita; Rahmawati, Dian Eka; Purwaningsih, Titin (Pusat Riset Politik BRIN, 2023)
Social media platforms have become one of the most important online spaces for political communication. The General Election Commission as the organizer of the election must be able to use social media to socialize the stages of the election that have been and will be held. By focusing on the use of Twitter in Indonesia, this research examines how the Indonesian General Election Commission is using the Twitter platform for socialization towards the 2024 general election. Researchers used a qualitative descriptive approach. The data is sourced from the KPU RI Twitter account with the account name @KPU_ID, then processed using Qualitative Data Software Analysis (QDSA), namely NVivo 12 Plus. The results show that the intensity of electoral content socialization delivered by KPU accounts has different intensities. The highest percentage of socialized content is Political Parties with 55%, Updating voter data at 17%, Formulation of Regulations at 16%, and Electoral districts with a percentage of 12%. However, while the intensity of KPU_ID tweets is very high, the reaction of followers to the presented content is very low because the information presented is not detailed. When using social media to communicate with their followers, KPU can provide a clear information reference to increase follower feedback. A clear reference to followers is crucial in exploring representational linkages between KPU and followers.